Microwave-assisted synthesis of ZnO/MWCNT hybrid nanocomposites and their alcohol-sensing properties - Prayut Potirak; Wisanu Pecharapa; Wichan Techitdheera (My University, 2013)
Zinc oxide and multi-walled carbon nanotube (ZnO/MWCNT) hybrid nanocomposites were synthesised by microwave-assisted method using the mixed solution of zinc acetate dehydrate (Zn(CH3COO)2·2H2O) and treated MWCNTs. The syntheses were carried out at various microwave irradiation powers. The characterisation of the as-synthesised nanocomposites was conducted by powder X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD results revealed that the composites were composed of two phases of MWCNTs and hexagonal wurzite ZnO. The SEM results showed that the ZnO nanoparticles were well decorated on the surface of MWCNTs. The amount of ZnO nanoparticles and their size increased with increasing irradiation power. Thick-film sensors were fabricated onto interdigitated conducting electrodes using as-synthesised hybrid composites as sensing materials. The alcohol-sensing behaviour of the hybrid composite films was investigated. The results indicated that the irradiation power had significant influence on the sensing response of the sensors toward alcohol. The sensor fabricated from the composite synthesised at higher irradiation power exhibited an enhanced alcohol-sensing performance.
Keywords: Advanced Chemical Sensor Technologies